Arabidopsis thaliana Sucrose Phosphate Synthase A2 Affects Carbon Partitioning and Drought Response - Laura Bagnato; Edoardo Tosato; Libero Gurrieri; Paolo Trost; Giuseppe Forlani; Francesca Sparla (Biology, 2023)
Sucrose is essential for plants for several reasons: It is a source of energy, a signaling molecule, and a source of carbon skeletons. Sucrose phosphate synthase (SPS) catalyzes the conversion of uridine diphosphate glucose and fructose-6-phosphate to sucrose-6-phosphate, which is rapidly dephosphorylated by sucrose phosphatase. SPS is critical in the accumulation of sucrose because it catalyzes an irreversible reaction. In Arabidopsis thaliana, SPSs form a gene family of four members, whose specific functions are not clear yet. In the present work, the role of SPSA2 was investigated in Arabidopsis under both control and drought stress conditions. In seeds and seedlings, major phenotypic traits were not different in wild-type compared with spsa2 knockout plants. By contrast, 35-day-old plants showed some differences in metabolites and enzyme activities even under control conditions. In response to drought, SPSA2 was transcriptionally activated, and the divergences between the two genotypes were higher, with spsa2 showing reduced proline accumulation and increased lipid peroxidation. Total soluble sugars and fructose concentrations were about halved compared with wild-type plants, and the plastid component of the oxidative pentose phosphate pathway was activated. Unlike previous reports, our results support the involvement of SPSA2 in both carbon partitioning and drought response.